Chlorophylls as Molecular Semiconductors: Introduction and State of Art (Adv. Mater. Technol. 2/2022). Issue 2 (8th February 2022) - Buscemi, Gabriella; Vona, Danilo; Trotta, Massimo; Milano, Francesco; Farinola, Gianluca M.
Abstract : Chlorophylls as Semiconductors Chlorophyll, shown as a racket, is the photochemical core of photosynthesis and its applications in organic electronics are raising large interest. The cover, representing the work in article 2100245 by Francesco Milano, Gianluca M. Farinola, and colleagues, depicts an electron exchanged between an artificial player and its natural counterpart on a court of chlorophylls layered on a transistor. The dazzling sun underlines the light‐triggered nature of the chlorophyll‐based hybrid devices.